Single Machine Production Scheduling Analysis Using FCFS, SPT, LPT, and EDD Methods To Increase Work Productivity in Furniture Companies - Farida Pulansari; Isna Nugraha (Future Science, 2024)
A furniture company has production scheduling problems by streamlining production output with one machine. This research aims to increase the work effectiveness of furniture companies by using a single machine and comparing several of the most efficient methods. The methods used are the FCFS, SPT, LPT, and EDD methods. From the research results of these four methods, it was found that the best method to use was the SPT method. However, there are still obstacles in the form of using a single machine which still really slows down the manufacturing process of a product. Products will still experience delays if the number of orders coming in increases. Therefore, a furniture company needs to add machines to reduce or minimize production delays that occur in the company. It would be better for future research to use other methods so that we can compare the results of another method.